Utilizing DDGS and crude glycerol in animal diets: feed manufacturing considerations - Mader, Erin F. (Kansas State University, 2011)
Three experiments were conducted to evaluate value added uses for dried distillers grains with solubles (DDGS) and crude glycerol in swine and poultry diets. In Exp.1, crude glycerol from multiple biodiesel production facilities was evaluated for storage and variability characteristics. Part one reviewed the storage capabilities of crude glycerol at room temperature and excessive heat conditions on ferrous and stainless steel metal. There was no notable corrosion during the two-month experiment for either metal type under each condition. There was a slight discoloration observed on the ferrous metal stored under excessive heat conditions, but no pitting or sign of corrosion was noted. No changes were observed in the stainless steel under either environment condition. Part two evaluated the variability of crude glycerol from multiple biodiesel production facilities. Representative samples of the parent feedstock and resultant glycerol was collected an analyzed. There was considerable variation between samples, particularly when comparing glycerol from the different feedstocks (vegetable vs. animal). Exp. 2 and 3 took place in the Feed Processing Research Center in the Department of Grain Science at Kansas State University. Pellet quality and electrical energy consumption was evaluated by reviewing production rate, conditioning and hot pellet temperatures, motor load, and pellet durability index (PDI) as testing parameters. In Exp. 2, diets containing varying levels of crude glycerol were evaluated on pellet quality and pellet mill performance in a pilot mill and in a commercial facility. For part one, a corn-soy based swine grower diet was formulated to contain 0, 3, 6, and 9% crude glycerol. Each diet was steam conditioned to 150, 170 and 190 °F in an atmospheric conditioner and pelleted. An interaction existed between glycerol and conditioning temperature. For all diets containing glycerol, roll skid occurred and the pellet mill plugged as conditioning temperature approached 190°F. Pellet quality increased linearly (P < 0.01) with increasing levels of glycerol. Part two took place at Don’s Farm Supply in Newell, IA. A corn-soy based turkey grower diet was formulated to contain 3% glycerol and pelleted. Results from part two were consistent with part one, in that there was an interaction between conditioning temperature and the addition of glycerol. Exp. 3 evaluated DDGS on pellet quality and electrical consumption. A poultry diet was formulated to contain 0, 15, or 30% DDGS and steam conditioned to 140, 160, and 180°F. As conditioning temperature increased, pellet quality in diets containing DDGS significantly improved (P>.001). Electrical consumption in diets containing DDGS compared to the control showed no significance in reduction in energy usage (P>.001). In conclusion, the production of pelleted diets containing crude glycerol is a feasible option; however, conditioning temperatures should be kept minimal and storage and variation of the material should be considered. In addition, improved pellet quality in pelleted diets containing DDGS is in part by conditioning at higher temperatures, respectively. The data suggests that the addition of crude glycerol and DDGS in animal diets can serve as a beneficial feed additive.
Keywords: Crude Glycerol; DDGS; Pellet Quality; Pellet Mill Performance; Variability; Storage; Agriculture, Animal Culture and Nutrition (0475)